DEVELOPING THE RELATIONSHIP BETWEEN PROCESS COST ACCOUNTING ALLOCATIONS AND THE ACCOUNTING RECORDS. - Usry, Milton F. (The Accounting Review, 1963)
Abstract It is possible that the student in his study of process cost accounting will acquaint himself with the techniques of cost allocations without grasping an understanding of just how these techniques fit into the accounting records. For this reason it is important that the student be required to prepare the cost transfer entries in connection with the process cost problems that he solves. An additional exercise that has been found to be most effective is the requirement that the student solve a problem that incorporates the matter of cost allocation as a segment of the overall accounting setting of a manufacturing concern. Many accounting textbooks fail to analyze completely the causes of a change in gross profit. Typically, any change is first divided into the change in sales and the change in cost of sales. Each of them in turn split into the change due to volume and the change due to unit prices or cost. It is not intended here that the traditional way is wrong from a practical analysis viewpoint. It is contended, however, that an effort should be made to show the student what the realities of the situation are, and why the practical approach is followed.